Insertion sequence elements of Pseudomonas savastanoi: Nucleotide sequence and homology with Agrobacterium tumefaciens transfer DNA - Yamada, Tetsuji (1986)
Two types of transposable elements, IS51 and IS52 (IS, insertion sequence), were found in Pseudomonas syringae subsp. savastanoi (P. savastanoi) that spontaneously insert into and inactivate iaaM; the insertion results in the loss of indoleacetic acid production and attenuation of virulence. The nucleotide sequences of both IS elements have sizes and structural features common to other prokaryotic IS elements; IS51 is 1311 base pairs (bp) long and has terminal inverted repeats of 26 bp; IS52 is 1209 bp long and has terminal inverted repeats of 10 bp with a 1 bp mismatch. In the insertion involving IS51, the trinucleotide sequence CAG is duplicated within iaaM sequences at the recombination junction; in those involving IS52 the tetranucleotide sequences TTAG or CTAG are duplicated within iaaM sequences at the recombination junction. A copy of IS51 occurs 2.5 kilobases downstream from IaaH. In contrast to the high copy number of IS51 in the genome of the bacterium, only a few copies of IS52 are present. No nucleotide sequence homology was found between IS51 and IS52. However, a striking nucleotide sequence homology was found between a 531-bp region of IS51 and a portion of the central region of transfer DNA (T-DNA) in the octopine plasmid pTi15955 from Agrobacterium tumefaciens. These observations, together with our earlier finding on the homology between iaaM and iaaH and between gene 1 and gene 2 of transfer DNA, further suggest that genes for indoleacetic acid production in the two systems have a common origin.